TANGGUNG JAWAB PENGURUS KOPERASI SIMPAN PINJAM BERBADAN HUKUM TERHADAP PENYIMPAN DANA - -, WIDIASTUTI (Wacana Hukum, 2009)
Abstract: A non well-managed cooperation has disadvantaged the creditor. It is caused by the difficulties to draw the fund from the debtors. But when the creditors ask to the court with the bad achievement reasons, the court refuse to conduct because the committee is not the party in the agreement. Therefore, it is necessary to construct fiduciary duty so that the committee who do not work properly can be put personal responsibility for this agreement. Key words: personal responsibility, fiduciary duty